2019
DOI: 10.1177/1555343419874248
|View full text |Cite
|
Sign up to set email alerts
|

The Divergence of Objective and Subjective Situation Awareness: A Meta-Analysis

Abstract: A review of 37 studies that included both objective and subjective measures of situation awareness (SA) was conducted. Objective and subjective measures of SA were found to diverge across a wide range of measurement techniques. Reasons for these differences include a lack of meta-awareness about one’s own SA, poor SA/confidence calibration, and confounds with workload among some measures. A model that shows how objective and subjective SA combine to affect performance is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 84 publications
5
49
0
Order By: Relevance
“…Observer ratings of SA overcome some problems with self-assessment, but still suffer from becoming a proxy for subjective performance ratings in that observers have limited information on a person’s mental representation of the situation. See also Endsley (in press).…”
Section: Introductionmentioning
confidence: 99%
“…Observer ratings of SA overcome some problems with self-assessment, but still suffer from becoming a proxy for subjective performance ratings in that observers have limited information on a person’s mental representation of the situation. See also Endsley (in press).…”
Section: Introductionmentioning
confidence: 99%
“…For example, usability comprises effectiveness and efficiency (behavioral) as well as satisfaction (attitude) in order to get a comprehensive product evaluation. Attitudes and behavior are often separate dimensions that do not match in different various areas of research [11,119,120]. For a comprehensive evaluation of HMIs and driving automation features from a Human Factors perspective, it might be necessary to include both of these data sources.…”
Section: Discussion Of Findings and Recommendations For Future Ad Stumentioning
confidence: 99%
“…SA measurement methods based on performance encounter problems with validity because performance and SA might be two different things (Nguyen et al, 2019 ). Endsley ( 2020 ) found that self-rating methods for SA measurements do not correlate with methods such as SAGAT, which aim to objectively measure SA knowledge. The author concluded that these methods measure different things, and self-rating methods should not be considered to measure the general SA.…”
Section: Situation Awareness and Its Measurementmentioning
confidence: 99%
“…Rather, they should be used to measure only the self-confidence about one's own SA. Combining low SA with high self-confidence might be especially dangerous (Endsley, 2020 ). Besides, methods based on self-rating after activity have the problem that the subject might have already forgotten details (Nguyen et al, 2019 ).…”
Section: Situation Awareness and Its Measurementmentioning
confidence: 99%
See 1 more Smart Citation